FACTORS AFFECTING THE GRAMMATICAL ERRORS MADE BY THE STUDENTS IN WRITING NARRATIVE PARAGRAPH - Senadaman Wau (Jurnal Education and Development, 2020)
The objective of the research was to know the factors that affecting the grammatical errors made by the students in writing narrative paragraph. This research was designed in qualitative research. This research was conducted at English Language Study Program of STKIP Nias Selatan. The data was collected by interviewing 15 students of fourth semester students. The students’ papers of writing narrative paragraph were the main source to determine the respondents of interview. Based on the data analysis, there were two factors that affecting the grammatical errors in writing narrative paragraph: first language interference and developmental errors. The research findings are expected becoming good information for the students and English lecturer to solve the students’ problems in writing narrative paragraph.